PREDIKSI EROSI TANAH DI SUB DAS MIU PADA KAWASAN TAMAN NASIONAL LORE LINDU (TNLL) - Pagiu, Salapu (FAPETKAN UNTAD, 2005)
Soil erosion, one of the major factors causing land degradation, has been increasing every year. It has brought about more critical land, more frequent fload on rainy season and drouht on dry season, over accumulation of sedimentation of dams and sea, all of these leading to functional lost of water facility. A research work was conducted from July to October 2002 to measure the level of soil erosion occurred in the enclave of Miu sub-catchmet in the area of the Lore Lindu Nasional Park in connection with the different land use system existing. The research results showed that the potential of land degradation was considerable in area where intensive human activities had occured. These areas encompassed included mixed plantations, shifting cultivation, shrubs and bushes. The levels of soil erosion were in the class III-IV. Attempts to reduce soil erosion rates through vegetative and soil conservation was a success as indicated by the sift of the level of soil erosion to the lowest class. Key words : Erosion, Lore-Lindu National Park